Pengaruh Transparansi, Partisipasi Dan Akuntabilitas Terhadap Kinerja Pengelolaan Alokasi Dana Desa Dan Dana Desa - Edi Yanto; Aqfir Aqfir (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
This research is a descriptive causal type of research with the aim of simultaneously and partially knowing the effect of transparency, participation and accountability on the performance of Village Fund Allocation Management (ADD) and Village Funds (DD) in Salumpaga Village, Tolitoli Utara District, Tolitoli Regency. The instrument used as a tool in making the conclusions of this study is a questionnaire consisting of several statements which are research indicators that have previously been tested for the validity and reliability of the instrument. The data analysis technique used is through multiple linear regression equations which emphasize the research hypothesis test. The results showed that there was no simultaneous and significant influence between transparency, participation, and accountability on the performance of village fund management. Likewise, the test of the spatial( partly ) , there is no significant influence between transparency , participation and accountability on the performance of the management of village fund allocations and village funds.